1300 Version Abnormalities of the Femur and Acetabulum in Patients with Femoroacetabular Impingement: A Systematic Review. (12th October 2021) - Arshad, Z; Maughan, H D; Pettit, M H; Kumar, K H S; Arora, A; Khanduja, V
Abstract: Aim: This systematic review aims to understand the relationship between version abnormalities of the femur and acetabulum in patients with primary and secondary femoroacetabular impingement (FAI). Method: A systematic review was conducted according to PRISMA guidelines. A computer-based search was performed using the EMBASE, MEDLINE, PubMed and Cochrane databases for articles relating to version and torsional abnormalities in FAI, Legg-Calve-Perthes disease (LCPD) and slipped capital femoral epiphysis (SCFE). The study was registered in the Open Science Framework. Two authors independently performed title/abstract and full text screening according to predetermined inclusion criteria. Results: A total of 1206 articles were identified 55 articles, involving 10, 091 hips, met the inclusion criteria. All studies evaluating femoral/acetabular version in FAI reported 'normal' mean version values (10 o to 25 o ). However, distribution analysis revealed that an estimated 31.4% and 51.3% of patients with FAI displayed abnormal acetabular and femoral version, respectively. Abnormal femoral version was reported in an estimated 74.5% of hips with LCPD, and abnormal acetabular version in an estimated 20%. Acetabular version was significantly lower in hips with SCFE compared to controls (Z=-3.26, P < 0.01). Conclusions: Patients presenting with hip pain attributed to FAI are likely to display an abnormality in femoral or acetabular version. This highlights the importance of evaluating these parameters during assessment of these patients, in order to guide clinical decision making.